Fonetisk transfer ved lukkelyde fra dansk L1 til spansk L2 hos danske gymnasieelever - Østergaard, Andreas F. K. (Journal of Language Works - Sprogvidenskabeligt Studentertidsskrift, 2023)
This study investigated the phonetic transfer from Danish as a first language (L1) to Spanish as a second language (L2) in the production of plosives in word-initial position. Danish plosives are voiceless and distinguished by their degree of aspiration, as opposed to a voicing distinction in Spanish. It was hypothesized that the feature of aspiration would be reproduced in the production of Spanish plosives by L1 Danish speakers due to transfer, which is the phenomenon in which a speaker unintentionally transfers characteristics from one language to another language in perception or production. In order to investigate this, the production of Spanish plosives by L1 Danish high school students was investigated. 27 high school seniors participated in a study in which they produced 18 sentences with word-initial plosives, which were recorded and analyzed acoustically. Recordings were also obtained from a native speaker of European Spanish for comparison. The study found that 74 % of participants with Danish L1 produced only voiceless plosives, and the ones who produced instances of voiced plosives did not do so consistently. This showed that, compared to the control participant, the VOT and degree of aspiration for the Danish L1 production of Spanish plosives were more acoustically like Danish plosives than Spanish ones. These findings, including small interviews conducted after the study, suggest that although the students are in their last year of education, most of them still have a pronunciation affected to a high degree by their native language. This finding is discussed in terms of theoretical models of L2 speech learning, in which it is suggested that more native-like productions of novel speech sounds may perhaps be achieved with the introduction of phonetic exercises such as high variability phonetic training (HVPT), as suggested in the L2LP-model (Elvin & Escudero 2019).